Right to leisure through play for refugee children in Egypt - Johnson, Carrie Leanna (AUC Knowledge Fountain, 2013)
Physical health programs specifically programmed for emotional rehabilitation are an important factor in post-trauma adjustment for refugee children in Egypt. This thesis explores definitions of the Right to Leisure, which can serve as a catalyst for such post-trauma rehabilitation for refugee children. Adequate access to the right to leisure is obstructed, however due to State-wide economic weaknesses, the failed implementation and reservations to various international treaties, xenophobia and discrimination, and the vast privatization of recreation spaces. Nonetheless, Egypt has consented to sharing international responsibility to safeguard the right to leisure for refugee children per several international treaties: the Convention on the Rights of the Child and the Refugee Convention. Egypt has also consented to similar rights expressed in the International Covenant of Economic and Social Rights and the African Charter. Considering Egypt’s economic incapacity, the State should act in good faith by vowing to not interfere with entities working to realize the right to leisure within the country. In fact, the Egyptian State must coordinate efforts with international organizations, universities and civil society to create access to the right to leisure within the country.